Long-term investigation of an open cluster Berkeley 65 - Chand, Tarak; Sharma, Saurabh; Singh, Koshvendra; Pandey, Jeewan; Verma, Aayushi; Kaur, Harmeen; Mamta,; Chakraborty, Manojit; Ojha, Devendra K.; Singh, Ajay Kumar (Frontiers in Astronomy and Space Sciences, 2025)
We present a decade-long investigation of a poorly studied cluster, Berkeley 65 (Be 65), using deep optical data from the telescopes of ARIES, Nainital Observatory. We estimate its radius (Rcluster = 1.6′, aspect ratio of ∼1.1), distance (2.0 ± 0.1 kpc) and age (∼160 Myrs). A clear turn-off point at ∼1.7 M⊙ in the mass function suggests the escape of low-mass stars, and the lower photometric mass compared to the dynamical mass indicates ongoing disruption due to external forces. Our long-baseline optical photometric data also identifies 64 periodic and 16 non-periodic stars in this region. We have presented the light curves and the classification of those variables. The periodic stars have periods ranging from ∼0.05 days to ∼3.00 days and amplitude ranges from ∼8 mmag to ∼700 mmag. The nonperiodic stars show variation from ∼30 mmag to ∼500 mmag. The periodic stars include main-sequence pulsating variables such as Slow Pulsating B-type, δ Scuti, RR Lyrae, and γ Doradus. We report a detached binary system and rotating variables similar to BY Draconis-type stars exhibiting variable brightness caused by starspots, chromospheric activity, and magnetic field-related phenomena.